2007
DOI: 10.1111/j.1460-9568.2007.05674.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the basolateral amygdala with the dorsal hippocampus and dorsomedial prefrontal cortex regulate drug context‐induced reinstatement of cocaine‐seeking in rats

Abstract: The basolateral amygdala (BLA), dorsomedial prefrontal cortex (dmPFC) and dorsal hippocampus (DH) are critical elements of the neurocircuitry of drug context-induced reinstatement of cocaine-seeking; however, little is known about functional interactions between these brain regions. The present study tested the hypothesis that serial information processing by the BLA and dmPFC mediates drug context-induced cocaine-seeking, whereas the BLA and DH independently control this behaviour. Rats were trained to self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
211
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(222 citation statements)
references
References 76 publications
11
211
0
Order By: Relevance
“…used a renewal design (Bouton and Bolles, 1979) and reported that rats trained to self-administer a heroin-cocaine mixture in one context, context A, and then extinguished in a second, different context, context B, showed a pronounced reinstatement of extinguished drug seeking when tested in context A. This context-induced reinstatement or renewal of extinguished drug seeking has since been reported for a variety of drug rewards including cocaine Fuchs et al, 2007;Hamlin et al, 2008), heroin (Bossert et al, 2004), alcohol Zironi et al, 2006;Hamlin et al, 2007;Marinelli et al, 2007), and nicotine (Diergaarde et al, 2008), as well as the natural reward sucrose (Hamlin et al, 2006). Renewal is a signature phenomenon of extinction (Bouton, 2002).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…used a renewal design (Bouton and Bolles, 1979) and reported that rats trained to self-administer a heroin-cocaine mixture in one context, context A, and then extinguished in a second, different context, context B, showed a pronounced reinstatement of extinguished drug seeking when tested in context A. This context-induced reinstatement or renewal of extinguished drug seeking has since been reported for a variety of drug rewards including cocaine Fuchs et al, 2007;Hamlin et al, 2008), heroin (Bossert et al, 2004), alcohol Zironi et al, 2006;Hamlin et al, 2007;Marinelli et al, 2007), and nicotine (Diergaarde et al, 2008), as well as the natural reward sucrose (Hamlin et al, 2006). Renewal is a signature phenomenon of extinction (Bouton, 2002).…”
Section: Introductionmentioning
confidence: 87%
“…It shows that extinction training does not erase the original learning that mediates drug seeking but instead imposes a mask on that learning to actively inhibit drug seeking in the extinction context. Studies using microinjections of dopamine and glutamate receptor antagonists, as well as reversible inactivation via baclofen/ muscimol or tetrodotoxin infusion, have implicated hippocampus, basolateral amygdala (BLA), nucleus accumbens shell (AcbSh), nucleus accumbens core (AcbC), ventral tegmental area (VTA), and dorsomedial prefrontal cortex (dmPFC) in contextinduced reinstatement of drug seeking (Bossert et al, 2004(Bossert et al, , 2006(Bossert et al, , 2007Fuchs et al, 2005Fuchs et al, , 2007Fuchs et al, , 2008. Recently, we have used c-Fos expression to identify the neural correlates of context-induced reinstatement.…”
Section: Introductionmentioning
confidence: 99%
“…During extinction training, lever responses were recorded but had no scheduled consequences. Before the fourth extinction-training session, rats were adapted to the intracranial microinfusion procedure, as described previously (Fuchs et al, 2007). As active lever responses during cocaine self-administration training averaged between 50 and 75/session (see Supplementary Table S1), extinction training continued until a criterion of p25 active lever responses/session on at least two consecutive days was reached.…”
Section: Cocaine Self-administration and Extinction Trainingmentioning
confidence: 99%
“…Active lever presses resulted in cocaine reinforcement (cocaine hydrochloride; 0.15 mg/0.05 ml per infusion, i.v. ; NIDA, Research Triangle Park, NC) under a FR-1/20 s-time-out schedule (Fuchs et al, 2007). Responses on the other (inactive) lever were recorded but had no scheduled consequences.…”
Section: Cocaine Self-administration and Extinction Trainingmentioning
confidence: 99%
See 1 more Smart Citation